2023
DOI: 10.1097/md.0000000000034365
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of LRRC1 in hepatocellular carcinoma and construction of relevant prognostic model

Abstract: This study aimed to elucidate the prognostic value of the leucine rich repeat containing 1 (LRRC1) gene in hepatocellular carcinoma (HCC) and to determine the effects of high and low LRRC1 expression on mutation and immune cell infiltration. We downloaded HCC mRNA-seq expression and clinical data from University of California Santa Cruz Xena. The expression of LRRC1 was compared between HCC tumor and normal samples. Tumor samples were divided according to high and low LRRC1 expression. Differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Recently, LRRC1, a cytoplasmic scaffold protein, was identified as an oncogenic factor that contributes to HCC [ 29 , 35 ] and lung cancer [ 32 , 36 ]; other studies have reported that LRRC1 regulates the stemness of breast cancer stem cells to behave as a potential tumor suppressor and that in human mesenchymal stem cells (MSCs) [ 33 ], LRRC1 acts as a downstream target of PPARγ that regulates adipocyte differentiation [ 30 ]. The results of these studies together emphasize the complex roles of LRRC1 in various pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LRRC1, a cytoplasmic scaffold protein, was identified as an oncogenic factor that contributes to HCC [ 29 , 35 ] and lung cancer [ 32 , 36 ]; other studies have reported that LRRC1 regulates the stemness of breast cancer stem cells to behave as a potential tumor suppressor and that in human mesenchymal stem cells (MSCs) [ 33 ], LRRC1 acts as a downstream target of PPARγ that regulates adipocyte differentiation [ 30 ]. The results of these studies together emphasize the complex roles of LRRC1 in various pathological processes.…”
Section: Discussionmentioning
confidence: 99%